2013
DOI: 10.1186/1756-0500-6-171
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cardiac changes in patients with systemic lupus erythematosus

Abstract: BackgroundThe aim of this study was evaluate the late-onset repercussions of heart alterations of patients with systemic lupus erythematosus (SLE) after a 13-year follow up.MethodsA historical prospective study was carried out involving the analysis of data from the charts of patients with a confirmed diagnosis of lupus in follow up since 1998. The 13-year evolution was systematically reviewed and tabulated to facilitate the interpretation of the data.ResultsForty-eight patient charts were analyzed. Mean patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
9
1
1
Order By: Relevance
“…Previous studies have also explored the prevalence of LV systolic dysfunction in patients with SLE, and when using the reduction of systolic function in standard echocardiographic parameters such as LVEF, it varied from 16% to 45%. [24][25][26] Initial studies have also shown an impairment of LV GLS in patients with SLE. Buss et al 6 showed, in 67 young patients with SLE, significant impairment in LV GLS compared with healthy control subjects, and similar results were obtained by Huang et al 7 in 34 consecutive patients with SLE.…”
Section: Systolic Dysfunction In Patients With Slementioning
confidence: 99%
“…Previous studies have also explored the prevalence of LV systolic dysfunction in patients with SLE, and when using the reduction of systolic function in standard echocardiographic parameters such as LVEF, it varied from 16% to 45%. [24][25][26] Initial studies have also shown an impairment of LV GLS in patients with SLE. Buss et al 6 showed, in 67 young patients with SLE, significant impairment in LV GLS compared with healthy control subjects, and similar results were obtained by Huang et al 7 in 34 consecutive patients with SLE.…”
Section: Systolic Dysfunction In Patients With Slementioning
confidence: 99%
“…Left-sided heart valves are by far the most affected. It has previously been reported to have cardiac involvement as the main reason for presentation; however, this is extremely rare [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is the best first modality to diagnose LSE, but transesophageal echocardiography is more sensitive and specific than transthoracic echocardiography [9,10]. Doppler echocardiography detects between 18% and 50% of valve diseases [1][2][3][4][5][6][7][8][9][10], while transesophageal echocardiography detects up to 74% [9,10]. LSE on imaging is described as irregular heterogeneous echo density with the absence of independent motion of the verrucous vegetations on the cardiac valves and endocardium [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The objective of this review was to present studies that used isometric exercise protocols and analyzed the cardiac autonomic response through HRV. Heart rate response during isometric exercise has been studied to understand cardiac autonomic control, since there is interaction between the cardiovascular, autonomic and muscular systems while performing exercise.…”
Section: B Discussionmentioning
confidence: 99%